The Motion Picture Editors Guild treatment of the film sound membership: enforcing status quo for Hollywood’s post-production sound craft - Andriano-Moore, Stephen (SAGE Publications Inc., 2020)
The Motion Picture Editors Guild (MPEG) is the labor union representing post-production workers in the Hollywood motion picture industry, including seven sound craft classifications. The sound craft has low status within the hierarchical structure of the Hollywood film industry in comparison to other filmmaking crafts. This article evaluates the workings of the MPEG in concerns with the sound craft and status within the industry through a thirty-plus year review of their professional journal, website, sound practitioner discourse, and other industrial documents. The article argues that the union does not sufficiently protect sound practitioners from employer exploitation, contributes to the alienation of sound practitioners from their work, and constraints the level of and recognition for creative contributions. These actions are seen as perpetuating the low status of sound practitioners and the sound craft, which weakens the power of the union.